Prospects of the construction of dam in semiarid brazilian and its implications in the region Seridó of the state of Rio Grande do Norte - Pereira Neto, Manoel Cirício (Sociedade & Natureza, 2017)
The construction of the water reservoirs in the Brazilian semiarid becoming one of the first engineering systems to “combat” or mitigate the effects produced by the drought phenomenon. The objective of this work is to analyze the perspectives that guide the policy of construction of dams over the years in the Brazilian semiarid, emphasizing the different implications for the region of Seridó Potiguar, considered one of the most densely damed of the country. It is observed that the the construction of dam in the Bra - zilian semiarid, and in particular the Seridó region, although initially designed mainly for human water supply and animal, inherent to the drought relief discourse, currently plays importants role of coexistence with this phenomenon, linked to other numerous economic, cultural and environmental activities of the regional scenario. There are several roles and outlooks related to the environmental context, the discourses and intentions of the different social, economic and statutory agents based on the conjecture, demands and complexities over time. Thus, it is important to insert, in parallel, to the debate on the policies and management of water resources in the Brazilian semi-arid region, and in particular on the Seridó region, the question of the multiple purposes related to the use and land subdivision of the area influence